Treatment of basal cell epithelioma which has been growing for many years – a case report - Daniel, Luiza; Leśniewski-Kmak, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2005)
Basal cell carcinoma ( Ca basocellulare, basal cell epithelioma, basalioma, rodent ulcer ) is the most common skin cancer. Skin cancers develop in sun-exposed areas and are common in men after the age of 40. Basal cell carcinoma is defined as slow-growing locally malignant epidermal skin tumour. It rarely spreads to the regional lymph nodes or distant organs: bone, lung and liver. The biopsy and CT or MRI are used for diagnosis and staging. There are six methods of treatment: cryotherapy, curettage and electrodesiccation, chemotherapy, surgical excision, micrographic surgery and radiation therapy. The choice of treatment is determined by factors such as the site and size of lesion, functional and cosmetic results, treatment time and cost, patient age and general condition. Primary radiotherapy is most often indicated for lesions on and around the nose, lower eyelids, and ears, where it yields better functional and cosmetic results than surgery. The large lesions close to the eye obtain 60–70 Gy in 30–35 fractions five days a week. The 8-years control rate in patients with carcinomas of the eyelid, nose and lip are 53%. The late effects of radiation therapy on the skin are: telangiectasia, atrophy, hypopigmentation, soft tissue necrosis and osteoradionecrosis. Radiotherapy can produce good cosmetic result and low risk of complications.